Analisis Semiotika Representasi Budaya Tionghoa dalam Film Crazy Rich Asians - Tjhing Tjhing; Yasinta Ariati (STARKI, 2022)
Film is a mass communication media that cannot be separated from the relationship between film and society. The Crazy Rich Asians movie directed by Jon M.Chu and writer by Kevin Kwan is not onlyfor the entertainment media of the audience but an education that provides insight and experience regarding the touch of history, culture, language, life of people of Chinese descent. For example about the inherent characteristics between the people of